The epigenetic regulator LSH maintains fork protection and genomic stability via MacroH2A deposition and RAD51 filament formation - Xu, Xiaoping (Nat Commun, 2021)
The Immunodeficiency Centromeric Instability Facial Anomalies (ICF) 4 syndrome is caused by mutations in LSH/HELLS, a chromatin remodeler promoting incorporation of histone variant macroH2A. Here, we demonstrate that LSH depletion results in degradation of nascent DNA at stalled replication forks and the generation of genomic instability. The protection of stalled forks is mediated by macroH2A, whose knockdown mimics LSH depletion and whose overexpression rescues nascent DNA degradation. LSH or macroH2A deficiency leads to an impairment of RAD51 loading, a factor that prevents MRE11 and EXO1 mediated nascent DNA degradation. The defect in RAD51 loading is linked to a disbalance of BRCA1 and 53BP1 accumulation at stalled forks. This is associated with perturbed histone modifications, including abnormal H4K20 methylation that is critical for BRCA1 enrichment and 53BP1 exclusion. Altogether, our results illuminate the mechanism underlying a human syndrome and reveal a critical role of LSH mediated chromatin remodeling in genomic stability.